Effect of Geometrical Structure to the Performance of Monolithic Dye–Sensitized Solar Cells - Bayu Aditya Nugraha; Shobih Shobih; Jojo Hidayat; Dahlang Tahir (Jurnal Elektronika dan Telekomunikasi, 2018)
Since invented for the first time, researchers in the world were focusing on how to increase the efficiency of dye-sensitized solar cells (DSSC) and reduce of the fabrication cost. Monolithic type of DSSC is one of the best solutions to reduce the fabrication cost due to the elimination of one of transparent conductive oxide (TCO) substrate. In this study, DSSC monolithic was fabricated layer by layer by using screen printing method. There are three layers that printed in each cell namely TiO2, ZrO2, and carbon before being injected with electrolytes. The geometrical structure of DSSC was varied to find the highest performance. From the I-V characteristics and incident photon-to-current efficiency (IPCE) characterization shows the highest efficiency is 0.137% and the highest conversion of photons to current occurs at around 510 nm wavelength, for a structure which has ZrO2 layer not crosses over the no-FTO area, while TiO2 layer half crosses the no-FTO area, this is most likely caused by the imperfection of the ZrO2layer.